In vitro inhibition of Hepatitis C virus protease and antioxidant by flavonoid glycosides from the Saudi costal plant Sarcocornia fruticosa. Issue 23 (2nd December 2019) - Hawas, Usama W.; Abou El-Kassem, Lamia T.; Shaher, Fekri; Al-Farawati, Radwan
Abstract: A new flavonol triglycoside, rhamnazin 3-O-2 G -rhamnorutinoside or rhamnazin 3- O -(2″, 6″- O -α-di-rhamnosyl)-β-glucoside (1 ) was isolated along with known flavonols, rhamnazin 3- O -rutinoside (2 ), rhamnazin 3- O -(6″- O -α-rhamnosyl)-β-galactoside (3 ), isorhamnetin 3- O -(6″- O -α-rhamnosyl)-β-galactoside (4 ), isorhamnetin 3- O -(2″, 6″- O -α-di-rhamnosyl)-β-galactoside (5 ), and isorhamnetin (6 ), and allantoin (7 ) from the aqueous methanol extract of Sarcocornia fruticosa leaves. Spectral analyses (UV, MS, and NMR) and acid hydrolysis were used to determine the structures. These compounds in this study except6 were reported for the first time from the genus Sarcocornia . The extract and flavonol glycosides (1–5 ) were evaluated for antioxidant and inhibition of HCV protease enzyme. Rhamnazin triglycoside (1 ) was shown to have a potent HCV protease inhibitor with IC50 value 8.9 μM, while isorhamnetin di- and triglycosides (4 and5 ) were effectively scavenged DPPH radicals with IC50 values 3.8 and 4.3 μM, respectively. Abstract :